Comparison of IL-6, IL-8 Concentrations in H. pylori- and non-H. pylori-associated Gastritis - Gontar Alamsyah Siregar; Sahat Salim; Ricky Rivalino Sitepu (The Indonesian Biomedical Journal, 2014)
BACKGROUND: Helicobacter pylori is a non-invasive microorganism causing intense gastric mucosal inflammatory and immune reaction. The gastric mucosal levels of the proinflammatory cytokines Interleukin 6 (IL-6) and IL-8 have been reported to be increased in H. pylori infection, but the serum levels in H. pylori infection is still controversial. The purpose of this study was to investigate the serum levels of IL-6 and IL-8 in H. pylori infection.METHODS: A cross sectional study was done on eighty consecutive gastritis patients admitted to endoscopy units at Adam Malik General Hospital and Permata Bunda Hospital, Medan, Indonesia from May-October 2014. Histopathology was performed for the diagnosis of gastritis. Rapid urease test for diagnosis of H. pylori infection. Serum samples were obtained to determine circulating IL-6 and IL-8. Univariate and bivariate analysis (independent t test) were done.RESULTS: There were 41.25% patients infected with H. pylori. Circulatory IL-6 levels were significantly higher in H. pylori-infected patients compared to H. pylori negative, but there were no differences between serum levels of IL-8 in H. pylori positive and negative patients.CONCLUSION: The immune response to H. pylori promotes systemic inflammation, which was reflected in an increased level of serum IL-6. Serum levels of IL-8 were not significantly different between H. pylori positive and negative.KEYWORDS: Helicobacter pylori, gastritis, IL-6, IL-8, cytokine